Colonization of the Intestinal Tract of Conventional Mice with Candida albicans and Treatment with Antifungal Agents - Turner, J. R. (1976)
Conventional mice inoculated with Candida albicans per os were unable to maintain this organism in the intestinal tract as judged by decreasing numbers of yeast recoverable from feces. After inoculation with 10(7) cells/mouse, fecal counts ranged from 10(5) cells per g of feces to 5 × 10(3) cells per g of feces during a 12-day experimental period. Addition of various antibiotics to the drinking water did not result in any improvement in maintenance or stability of the gut population. A combination of X irradiation and administration of tobramycin or gentamicin, however, resulted in a stable population of C. albicans in the intestinal tract, with cell counts in the feces remaining constant at a level of about 10(6)/g of feces for a period of 10 to 15 days. The usefulness of this model in assessing the effect of experimental drugs on C. albicans infections of the gut was demonstrated by the fact that treatment with a new antifungal antibiotic (A9145), amphotericin B, 5-fluorocytosine, or nystatin resulted in a reduction in the fecal counts of C. albicans from experimentally infected animals.